СЎНГГИ ДАВРДА ЎЗБЕК ХАЛҚ ДОСТОНЛАРИНИ ЎРГАНИШНИНГ ЛИНГВИСТИК АСОСЛАРИ - Нурбоев, Ш. (SCIENCE and SOCIETY, 2022)
The article provides a brief analysis of doctoral, candidate, master’s theses defended in the field of Uzbek linguistics over the past decade, as well as scientific ideas in the dictionaries of published large monographic studies, new ideas. The scientific novelty of the study lies in a comprehensive approach to the analysis of lexical material, which is devoted to issues raised in individual studies, in particular, the relationship of the lexical material of folk epics to the dialect and literary language.